2019
DOI: 10.1080/13880209.2019.1643378
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities, isolated compounds and HPLC profile of Verbascum nubicum

Abstract: Context: Genus Verbascum (Scrophulariaceae) comprises about 360 species of flowering plants. Verbascum has been used in traditional medicine as an astringent, antitussive, analgesic and anti-inflammatory. Objective: Nothing was found in the available literature concerning Verbascum nubicum Murb; therefore, the study evaluates the biological activities, isolated compounds and HPLC profile. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…Although there is no direct evidence that RES-CMCS affects insulin release in obese diabetic rats, activation of β -cell electrical activity by RES-CMCS could potentially stimulate insulin release. This result is consistent with previous findings 47 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Although there is no direct evidence that RES-CMCS affects insulin release in obese diabetic rats, activation of β -cell electrical activity by RES-CMCS could potentially stimulate insulin release. This result is consistent with previous findings 47 .…”
Section: Discussionsupporting
confidence: 94%
“…Our results were in agreement with those of El Gizawy et al 47 , who found that dietary resveratrol supplementation lowered the levels of low plasma density lipoprotein, very low-density lipoprotein, and total cholesterol in liver rats. Lower levels of plasma cholesterol as well as triacylglycerol-fed rats may be connected to changes in the activity of two essential en-zymes in cholesterol metabolism, HMG-CoA reductase and cholesterol 7-hydroxylase.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, some species of the plant are reported to have expectorant, mucolytic and sedative properties used in the treatment of respiratory ailments such as bronchitis, tuberculosis, and asthma [3]. Verbascum nubicum Murb species showed significant hepatoprotective, antiinflammatory, and antioxidant effects [4]. Verbascum bombyciferum Boiss inhibited several enzymes, including acetylcholinesterase and butyrylcholinesterase [5].…”
Section: Introductionmentioning
confidence: 99%
“…HMGB1 represents a major challenge to improve the treatment of acute/chronic inflammation as well as infection and ischemia-reperfusion-induced injury. Many studies prove that the developing of HMGB1 inhibitors like natural products [11][12][13] .…”
mentioning
confidence: 99%